One-step synthesis and performance evaluation of zinc metavanadate pigments as highly anticorrosive primers - Dang Quang Vinh Nguyen; Tien Khoa Le; Thi Thanh Thuy Nguyen (Vietnam Journal of Science, Technology and Engineering, 2020)
Recently, the vanadate species have been considered as promising inhibitor agents used for metal protection. Various metallic materials were treated in a vanadate solution in order to form a passivation coating. However, the use of solid vanadate compounds as inhibitor pigments in the formulation of anticorrosive primers is still limited. Therefore, in this work, solid zinc metavanadate pigments for application in paint primers were prepared by a simple route at various pH values and concentrations of monovanadate. According to the results, all samples showed a characteristic hexagonal structure with high anticorrosive abilities. Both the pH and monovanadate concentration strongly affected the morphology, the particle size, and the anticorrosion power. Among the prepared samples, the best anticorrosive pigment was the sample prepared at pH 8 with a vanadate concentration of 0.2 M.